Implementation Unified Modeling Language in the Development E-mail Application System - Aprijal, Aprijal; Hindarto, Djarot (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2023)
In the era of globalization, which is influenced by advances in technology and information, several government institutions, such as Bank XYZ Head Office, still use a semi-computerized approach in the archiving process, especially in documenting incoming and outgoing letters. As a result, data entry errors often occur, resulting in inaccurate reports. To overcome this problem, the author proposes a new method that involves analysis, planning, and design procedures using the PHP programming language and MySQL database, as well as an object-oriented approach by utilizing the Unified Modeling Language during the implementation stage. With this new system, errors in recording incoming and outgoing mail will be reduced, and data processing will become more efficient so that reporting can be consistent with existing data. Application system testing is carried out to determine that the system designed and developed meets the needs of users and company management. From testing these modules, success = 93,33% and failure = 6,67%.Keyword: PHP programming language; Unified Modeling Language; MySQL database Â AbstrakDi era globalisasi yang dipengaruhi oleh kemajuan teknologi dan informasi, beberapa institusi pemerintahan seperti Kantor Pusat Bank XYZ masih menggunakan pendekatan semi komputerisasi dalam proses pengarsipan, khususnya dalam pendokumentasian surat masuk dan keluar. Akibatnya, kesalahan entri data sering terjadi sehingga menghasilkan laporan yang tidak akurat. Untuk mengatasi masalah ini, penulis mengusulkan metode baru yang melibatkan prosedur analisis, perencanaan, dan desain menggunakan bahasa pemrograman PHP dan database MySQL serta pendekatan berorientasi objek dengan memanfaatkan Unified Modeling Language selama tahap implementasi. Dengan sistem baru ini diharapkan kesalahan dalam pencatatan surat masuk dan keluar akan berkurang, dan pengolahan data menjadi lebih efisien sehingga pembuatan laporan dapat konsisten dengan data yang ada. Pengujian system aplikasi dilakukan untuk mengetahui bahwa system yang dirancang dan dikembangkan sudah memenuhi kebutuhan user dan manajemen perusahaan. Dari pengujian modul-module tersebut sukses = 93,33% dan gagal = 6,67%.Â